KONSEP PENDIDIKAN ANAK DALAM AL QUR’AN (ANALISIS TAFSIR TARBAWI QS. LUQMAN AYAT 12-15) - Ahmad Irfan; Ummah Karimah; Ayuhan Ayuhan; Risdianto Risdianto; Amriani Amriani; Nurul Husna; Nida Nadhifatul Jannah (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2023)
Education is the main aspect that can have an impact on the survival of individuals. For this reason, the right time to start education is during childhood. Children are parents' investment in the hereafter. So that children's education will be the main concern, especially in the aspect of Islamic education. The Qur'an is the main source of reference, collected in it various explanations of the concept of education. This study aims to determine the concept of child education in the Qur'an surah Luqman verses 12-15 through tarbawi tafsir analysis by presenting lughowi analysis according to the opinions of the mufassirs. The research method used is library research with a descriptive qualitative approach. The results of data analysis found that: (1) Education given to children is tawhid education, namely introducing the oneness of Allah SWT, worship education as an embodiment of tawhid education and moral education, one of which is doing good to both parents. (2) Child education is carried out with good communication and language full of affection, like Luqman who calls his son "yabunayya"